Hukum Keluarga Di Indonesia Dalam Fatwa Bahsul Masail Nahdlatul Ulama (NU) - Mentari, Vennya Agna; Havid, Trio Lukmanul; Aripin, Iiz Tazul; Mufti, Zaenul; Jamarudin, Ade (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Fatwa is a legal opinion issued by a mufti in response to a question or problem related to Islamic law. Fatwas are based on the Qur'an, hadith, ijma' and qiyas. This paper also highlights the role of fatwas in resolving contemporary legal problems faced by Muslim communities in Indonesia. This study uses a normative-juridical approach and secondary data sources to analyze fatwa on family law issued by the Nahdlatul Ulama organization. This paper discusses the legal implications of several issues such as the law on marriage for married men who claim to be single and the law on abortion due to rape. This paper also provides criteria for determining whether divorce is valid or not and the importance of understanding the intentions and circumstances involved in divorce cases. This paper quotes various scholars and fatwas from the National Ulema Conference and the Nahdlatul Ulama organization.Keywords: Fatwa, Islamic law and Nahdlatul Ulama. Abstrak: Fatwa adalah pendapat hukum yang dikeluarkan oleh seorang mufti sebagai jawaban atas pertanyaan atau masalah yang berkaitan dengan hukum Islam. Fatwa didasarkan pada Al-Qur'an, hadis, ijma', dan qiyas. Tulisan ini juga menyoroti peran fatwa dalam menyelesaikan masalah hukum kontemporer yang dihadapi oleh masyarakat Muslim di Indonesia. Studi ini menggunakan pendekatan yuridis-normatif dan sumber data sekunder untuk menganalisis fatwa tentang hukum keluarga yang dikeluarkan oleh organisasi Nahdlatul Ulama. Tulisan ini membahas implikasi hukum dari beberapa masalah seperti hukum pernikahan lelaki beristri yang mengaku lajang dan hukum aborsi karena perkosaan. Tulisan ini juga memberikan kriteria untuk menentukan sah atau tidaknya talak dan pentingnya memahami niat dan keadaan yang terlibat dalam kasus perceraian. Tulisan ini mengutip berbagai ulama dan fatwa dari Konferensi Ulama Nasional dan organisasi Nahdlatul Ulama.Kata kunci: Fatwa, hukum Islam dan Nahdlatul Ulama.